The Problems of Upbringing in Hakob Paronyan’s Children’s Periodical - SOGHOYAN, ASTGHIK (Bulletin of Yerevan University B: Philology, 2021)
The article touches upon the study of “Theater: A Friend to Children” by Hakob Paronyan. It focuses on the analysis of the educational role of children’s weekly newspaper and on formation of gender identity in the context of children reading it and also refers to the concept by which Paronyan has turned to the role distribution of schoolchildren and to the shaping of heroes of both sexes by giving each of them separate functions and thus forming the members of the future society. The characters of boys and girls in the works of Paronyan for children are not monosemic: these heroes have vital functional differences that are conditioned by the social mentality of the time, social preconditions and personal perceptions and beliefs of the author which are expressed through characters (temper, the framework of activities, environment, implemented functions, punishments), images and lessons given by theauthor. The core task of the study is the analysis of the issues which play the utmost role from the concept of psychological, functional and descriptive problems and also their possible impact on the upbringing of the Armenian children the in the late 19th century.